A Hardware‐Based String Matching Using State Transition Compression for Deep Packet Inspection. Issue 1 (1st February 2013) - Kim, HyunJin; Lee, Seung‐Woo
Abstract : This letter proposes a memory‐based parallel string matching engine using the compressed state transitions. In the finite‐state machines of each string matcher, the pointers for representing the existence of state transitions are compressed. In addition, the bit fields for storing state transitions can be shared. Therefore, the total memory requirement can be minimized by reducing the memory size for storing state transitions.